Serum Trace Elements ( Se+2, Cu+2, Zn+2) in Patients with Behcet's Disease - AL-Joofy, Ikbal Kh.; mousawy, Kalida M.; muslih, Raad K.; Al-wazi, Makram M. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Extensive reports denote the biological role of trace elements (Cu Zn ", Se ') in many various physiological and pathological conditions, one of the list is shown to be Behcet's disease (BD).The aim of this study was directed towards the distribution of trace elements (Cu 2,Zn, 2,Se 2) in sera of BD patients, and control groups.Methods: Fifty Arab Iraqi patients who fulfdled the ISO criteria for diagnosis BD.compared with 21 patients control with recurrent oral ulcer (ROU), healthy control groups (2Ihealthy relative and 21healthy volunteer). Typing HLA Class I was carried out at Alkarama hospital, by using microlympho-cytotoxicity test. The concentrations of serum Cu ', Zn ", and Se" were determined by atomic absorption spectrophotometry.Result: Variation in levels of these trace elements as significant (P < 0.001) in Cu+2concentral and decreased (P